2019
DOI: 10.1136/bmjopen-2018-028226
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for acute exacerbation of idiopathic pulmonary fibrosis: protocol for a systematic review and meta-analysis

Abstract: IntroductionIdiopathic pulmonary fibrosis (IPF) is a form of chronic fibrosing interstitial pneumonia with unknown disease aetiology. Acute exacerbation (AE) of IPF is an accelerated disease progression beyond its expected course. A 30-day mortality of AE of IPF is 40%. While death may occur, there is much variation in the clinical progression of this condition. Previous attempts have been made to investigate various possible prognostic factors for AE of IPF; however, they have yet to be confirmed. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The methodology of this review may have affected the selection and confirmation of prognostic factors although it had been reported in a protocol paper beforehand. 21 Potential prognostic factors were defined as any clinical information reported in three or more studies assuming that frequent reports would likely imply clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology of this review may have affected the selection and confirmation of prognostic factors although it had been reported in a protocol paper beforehand. 21 Potential prognostic factors were defined as any clinical information reported in three or more studies assuming that frequent reports would likely imply clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…20 The methods were described briefly as the in-depths of methodology of this study were reported as a protocol paper beforehand. 21 Patient and public involvement There was no patient and public involvement in the whole process of conducting this research.…”
Section: Methodsmentioning
confidence: 99%
“…Randomised clinical trials (RCTs) are often classified as "high quality" evidence regarding efficacy of new treatments for patients with a specific disease, whereas case reports and other observational data are considered as hypothesis generators with initially classified lower grade of evidence (69)(70)(71)(72). However, an increasing argument is being made in defense of case reports and its restoration as a prominent and useful medical reporting strategy (73).…”
Section: Discussionmentioning
confidence: 99%
“…The phase of investigation GRADE domain is a district for prognostic studies phase 3 and phase 2 considered the highest quality of evidence 53. The GRADE system will be applied to assess the overall quality of evidence of confirmed prognostic factors generated from univariate results, as used previously 55…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…The overall decision of judging whether a factor is prognostic will be based on two criteria, an approach used previously 55. First, the same factor must show statistical univariate association with an outcome in at least 75% of all included studies.…”
Section: Eligibility Criteriamentioning
confidence: 99%